POWER PREDICTED FROM WASTE HEAT RECOVERY EXHAUST OF NATURAL ASPIRATED ENGINE - Herawan, Safarudin Gazali; Abdul Hakim, Rohhaizan; Ahmad Faris, Ismail; Mohammed, Ataur Rahman (2013)
The utilization of exhaust waste heat is now well known and the basic of many combined cooling, heating, and power installations. Heat recovery from automotive engines has seen predominantly for turbo-charging or others such as cabin heating, thermoelectric, and air conditioning. The exhaust gases from such installations represent a significant amount of thermal energy that traditionally has been used for combined heat and power applications. This paper explores the theexperimetall performance and simulation of natural aspirated spark ignition engine model of 1.6 L, which is occupied with waste heat recovery mechanism (WHRM). The experimental and simulation test results suggest that the concept is thermodynamically feasible and could significantly enhance system performance depending on the load applied on the engine. The simulation method is created using artificial neural network that can predicted the power produced from the WHRM.